Bosnia and the Middle East: Current Political, Economic and Cultural Ties. Issue 2 (2nd April 2016) - Bishku, Michael B.
Abstract: This article will review and analyze Bosnia's political, economic and cultural ties with the Middle East, most especially Turkey, Iran, Saudi Arabia and Israel, as well as the evolution of Muslim identity in that republic, especially since the late 1960s when there was an internal liberalization process in part influenced by Yugoslavia's policy on non-alignment. Today, Bosnians of all ethnic and religious backgrounds must contend with internal divisions and tensions exacerbated by the 1992–1995 war while utilizing a very cumbersome political system that may have brought peace at the expense of unity. Bosnia's geographical location draws that country toward the rest of Europe while history and the legacy of the Ottoman Empire, also draws Muslims toward the Middle East.